Advanced pharmacokinetic models based on organ clearance, circulatory, and Fractal concepts - Pang, K. Sandy; Weiss, Michael; Macheras, Panos (AAPS JOURNAL, 2007)
Three advanced models of pharmacokinetics are described. In the first class are physiologically based pharmacokinetic models based on in vitro data on transport and metabolism. The information is translated as transporter and enzyme activities and their attendant heterogeneities into liver and intestine models. Second are circulatory models based on transit time distribution and plasma concentration time curves. The third are fractal models for nonhomogeneous systems and non-Fickian processes are presented. The usefulness of these pharmacokinetic models, with examples, is compared.
Keywords: based pharmacokinetic; circulatory models; distribution; fractal models; homogeneous; Kidney; Liver; Models; nonhomogeneous; PBPK; pharmacokinetic models; physiologically